a look at the university transformation (Revista Electrónica REDINE, 2018)
Already approximately two decades (in the 80s) that is introduced in the education sector and the productive to the need to link education with the performance. The gap between both sectors showed at that time and even in the present, need to incorporate an educational modality, demanding that this be made more according to the real needs of the environment, with a greater presence not only of institutional and pedagogical content, but also in the evaluation of the results to be based on performance showing individuals once they have completed their training in the curriculum  of studies in the educational system and which in turn allowed the demonstration of their skills and their performance doomed in the University transformation.
Keywords: college transformation; competencies and performance